Thyroid Hormones in the Brain and Their Impact in Recovery Mechanisms After Stroke - Talhada, Daniela; Santos, Cecília Reis Alves; Gonçalves, Isabel; Ruscher, Karsten (Frontiers in Neurology, 2019)
Thyroid hormones are of fundamental importance for brain development and essential factors to warrant brain functions throughout life. Their actions are mediated by binding to specific intracellular and membranous receptors regulating genomic and non-genomic mechanisms in neurons and populations of glial cells, respectively. Among others, mechanisms include the regulation of neuronal plasticity processes, stimulation of angiogenesis and neurogenesis as well modulating the dynamics of cytoskeletal elements and intracellular transport processes. These mechanisms overlap with those that have been identified to enhance recovery of lost neurological functions during the first weeks and months after ischemic stroke. Stimulation of thyroid hormone signaling in the postischemic brain might be a promising therapeutic strategy to foster endogenous mechanisms of repair. Several studies have pointed to a significant association between thyroid hormones and outcome after stroke. With this review, we will provide an overview on functions of thyroid hormones in the healthy brain and summarize their mechanisms of action in the developing and adult brain. Also, we compile the major thyroid-modulated molecular pathways in the pathophysiology of ischemic stroke that can enhance recovery, highlighting thyroid hormones as a potential target for therapeutic intervention.